Enzymatic production of biodiesel from Nannochloropsis gaditana lipids: Influence of operational variables and polar lipid content. (July 2015) - Navarro López, Elvira; Robles Medina, Alfonso; González Moreno, Pedro A.; Jiménez Callejón, María J.; Esteban Cerdán, Luis; Martín Valverde, Lorena; Castillo López, Beatriz; Molina Grima, Emilio
Highlights: Saponifiable lipids (SLs) were extracted from wet microalgal biomass. SLs were transformed to biodiesel by lipase catalyzed transesterification. The importance of polar lipids and SL purity for biodiesel conversion is showed. Influence of solvent and methanol/SL ratio on lipase stability is discussed. 94.7% of microalgal SLs were transformed to biodiesel in the optimized conditions. Abstract: Fatty acid methyl esters (FAMEs, biodiesel) were produced from Nannochloropsis gaditana wet biomass (12% saponifiable lipids, SLs) by extraction of SLs and lipase catalyzed transesterification. Lipids were extracted by ethanol (96%)–hexane, and 31% pure SLs were obtained with 85% yield. When the lipids were degummed, SL purity increased to 95%. Novozym 435 was selected from four lipases tested. Both the lipidic composition and the use of t-butanol instead of hexane increased the reaction velocity and the conversion, since both decreased due to the adsorption of polar lipids on the lipase immobilization support. The best FAME yield (94.7%) was attained at a reaction time of 48 h and using 10 mL of t-butanol/g SL, 0.225 g N435/g SL, 11:1 methanol/SL molar ratio and adding the methanol in three steps. In these conditions the FAME conversion decreased by 9.8% after three reaction cycles catalyzed by the same lipase batch.